Evaluation of the Activetalk English Proficiency Programme among Franchisors, Parents, Teachers and Student in Selangor, Malaysia - Ng, Thiam Huat (2023)
The issue of English language proficiency for children born with different mother tongue has long been a focus of educational research and a recurring debate in public education systems. It is also related to the underpinning theory of learning English as a second language for Malaysian children because of the country’s historical roots under British colonial rule and its multiracial and multilingual population of Malays, Chinese, Indians and other ethnic East Malaysia communities. Public schooling systems, that is, government schools are not be able to meet the demand requirement of students of various ethnic and different income groups for English language classes due to limited resources and tight schooling-time schedule. Hence, the demand to fulfil need for private tuition or delivery of English language classes fell into the language-franchise operators throughout the country. Specially, the purpose of the study is to examine the way to fill the demand gap to better prepare mother tongue-need children to learn and acquire the English language proficiency through the Selangor Activetalk English in Malaysia, as the pioneering initiative before its subsequent expansion into other Malaysia states. The target population and sample in this qualitative approach are focused on children and adolescence between the ages of 3 to 17 years old. The interview questionnaire and the respondent-participants therefrom provided the finding-results feedback for content analysis, thematic analysis and conclusion synthesis based on responses from the Activetalk EnglishCentre franchiser, its franchisee-license managers, teachers, students and parents from the current total of 7-active Activetalk English Centres throughout the State of Selangor. Overall, the result-outputs suggest that Activetalk English so far is performing well, with a reasonable steady income stream of committed teachers who are satisfied with their remuneration package based on their Activetalk teaching materials, the latter having positive feedback from parents and children who have successfully and competitively engaged in term-end or year-end pubic-speaking contests in public places such as popular and new commercial complexes of Shopping-Malls. The output-outcome suggests that the potential for promoting more subscribers (as parental-children-clients or franchisee-investors) to Activetalk English is yet fully unexplored. In this direction, future plans include a new Activetalk English Centre to be located within the premises of a Subang Jaya international university building to capture the market segmentation in this resident-commercial area in the State of Selangor.